Preparation method and application of Cu modified SAPO-34 composite material
Through the preparation of Cu-modified SAPO-34 composite material, the problems of agglomeration and insufficient stability of Cu-SAPO-34 catalyst are solved, and efficient low-temperature denitrification and water-resistant sulfur resistance are achieved, which are suitable for nitrogen oxides of automobile exhaust gases Elimination.
Patent Information
- Application Number
- CN202411413957.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-11
- Publication Date
- 2025-01-14
- Estimated Expiration
- 2044-10-11
AI Technical Summary
The active sites of the existing denitrification molecular sieve catalyst Cu-SAPO-34 are prone to agglomeration, have poor low temperature activity, poor hydrothermal stability, and insufficient water and sulfur resistance, which cannot effectively eliminate nitrogen oxide pollution in automobile exhaust.
The preparation method of Cu modified SAPO-34 composite material was used, and the synthesis was performed by one-step hydrothermal method, using copper acetylacetonate, copper glycine or copper ethylenediamine dihydroxide as the copper source, and tetraethylene pentamine (TEPA) as the dispersant and Pore-forming agent forms a catalyst with atomic dispersed Cu active site, improving the low-temperature activity and stability of the catalyst.
Achieve high-efficiency denitrification conversion rate (90%-100%) in the range of 150℃~430℃, and maintain excellent reactivity under high temperature hydrothermal conditions, with good water and sulfur resistance, suitable for nitrogen oxidation of automobile exhaust gas Elimination of things.
Smart Images

Figure CN119303623A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to a method for preparing a catalyst for selective catalytic reduction of NO, and belongs to the field of selective catalytic reduction of NO. Background Art
[0002] With the rapid development of human activities and the continuous improvement of living standards, people are paying more and more attention to environmental issues. At present, the main environmental problems we face are of two types: one is the original environmental problems caused by the evolution of nature and natural disasters, also known as the first environmental problems. The other is the environmental problems caused by human activities, also known as the second environmental problems, which are divided into two categories: environmental pollution and ecological damage. At present, the emission of nitrogen oxides in automobile exhaust, especially the emission of diesel exhaust, is particularly prominent in polluting the atmosphere.
[0003] Catalytic selective reduction of ammonia (NH3-SCR) is considered to be an effective technology for eliminating nitrogen oxide pollution. Existing denitrification catalysts can be roughly divided into three categories: precious metal catalysts, metal oxide catalysts, and molecular sieve catalysts. The CO produced by the incomplete combustion of fuel by precious metal catalysts can easily lead to poisoning and deactivation of the active components of precious metal catalysts, and the high cost limits its further development; metal oxide catalysts, such as V2O5-WO3(MoO3) / TiO2, have the disadvantages of high NO complete conversion temperature, limited operating temperature window, and biological toxicity of V species, which are not suitable for the elimination of automobile exhaust nitrogen oxides; commonly used molecular sieve catalysts are Cu-SAPO-34 and Cu-SSZ-13, but both have the problems of easy agglomeration of active species Cu, poor low-temperature activity, poor water resistance, and poor hydrothermal stability. Summary of the invention
[0004] The present invention aims to solve the technical problems of the existing denitration molecular sieve catalyst Cu-SAPO-34, such as easy agglomeration of active sites, poor low-temperature activity, poor hydrothermal stability, and poor water and sulfur resistance, and to provide a preparation method and application of a Cu-modified SAPO-34 composite material.
[0005] The preparation method of the Cu-modified SAPO-34 composite material of the present invention is carried out according to the following steps:
[0006] 1. Weigh pseudo-boehmite, H3PO4, white carbon, triethylamine (TEA), tetraethylenepentamine (TEPA), and copper organic complex;
[0007] The mass ratio of pseudo-boehmite to white carbon is (1.1-2.7):1;
[0008] The volume ratio of H3PO4 to the mass of white carbon black is (1.3-2) mL: 1 g;
[0009] The copper organic complex is copper acetylacetonate, copper glycinate or copper ethylenediamine dihydroxide;
[0010] First, dissolve pseudo-boehmite in deionized water and stir on a magnetic stirrer at room temperature for 0 to 4 hours; then add H3PO4 and continue stirring for 0 to 4 hours; then add white carbon black and continue stirring for 2 to 2.5 hours; then add triethylamine (TEA) and continue stirring for 0 to 4 hours; then add tetraethylenepentamine (TEPA) and stir for 2 to 2.5 hours; finally, add copper organic complex and stir for 8 to 16 hours to obtain sol-gel;
[0011] 2. After ultrasonic treatment, the sol-gel obtained in step 1 is transferred to a hydrothermal reactor, and then the hydrothermal reactor is placed in an oven at a temperature of 180-200° C. for 24-48 hours for hydrothermal reaction, and the product is washed with deionized water and ethanol in turn, centrifuged and dried to obtain a precursor;
[0012] 3. After the precursor is ground into powder, it is placed in a porcelain boat, placed in a muffle furnace, heated to 550-580°C, and calcined for 5-6 hours to obtain a Cu-modified SAPO-34 composite material, recorded as Cu-SAPO-34.
[0013] Furthermore, the mass percentage of Al2O3 in the pseudo-boehmite described in step 1 is ≥ 70%.
[0014] Furthermore, the mass percentage of SiO2 in the white carbon black described in step 1 is ≥85%.
[0015] Furthermore, the ratio of the mass of the white carbon black described in step 1 to the volume of triethylamine (TEA) is 1 g: (3.3-6.7) mL.
[0016] Furthermore, the ratio of the mass of the white carbon black described in step 1 to the volume of tetraethylenepentamine (TEPA) is 1 g: (1.3-2) mL.
[0017] Furthermore, the mass ratio of white carbon black to copper acetylacetonate described in step 1 is 1:(0.6-1.4).
[0018] Furthermore, the mass ratio of white carbon black to copper glycinate described in step 1 is 1:(0.5-1).
[0019] Furthermore, the ratio of the mass of the white carbon black described in step 1 to the volume of copper dihydroxide of ethylenediamine is 1 g: (3.3-6.7) mL.
[0020] The application of the Cu-modified SAPO-34 composite material prepared by the above method is to use the Cu-modified SAPO-34 composite material as a catalyst in the NH3-SCR denitration reaction.
[0021] The advantages of the present invention are as follows:
[0022] (1) The present invention synthesizes and prepares Cu-SAPO-34 by a one-step hydrothermal method, which is simple to operate, short in time, low in cost, high in yield, and can be mass-produced.
[0023] (2) The present invention uses copper acetylacetonate, copper glycinate, and copper dihydroxide ethylenediamine as copper sources. The organic structure in the copper organic complex is conducive to coordination with the silanol and aluminum hydroxyl groups in the molecular sieve to form Cu-SAPO-34 with atomic-level dispersed Cu active sites. Cu is not easy to agglomerate during the reaction, thereby improving the low-temperature activity and stability of the reaction. At the same time, the active substance copper in the catalyst is more evenly dispersed, and more copper species are located in the six-membered ring and eight-membered ring of the active site of the molecular sieve, and the content of active species copper can be controlled.
[0024] (3) The purpose of tetraethylenepentamine (TEPA) in the present invention is a dispersant and pore-forming agent, rather than a common template agent. The addition of TEPA promotes the dispersion of copper; at the same time, a multi-level pore structure is formed, which is beneficial to mass transfer and eliminates internal diffusion restrictions, thereby improving the reaction activity.
[0025] (4) The Cu-SAPO-34 catalyst prepared by the present invention exhibits extremely excellent low-temperature SCR activity in the NH3-SCR reaction, and the denitration conversion rate can reach 90% to 100% at 150°C to 430°C. It also has N2 selectivity, and can still maintain good reaction activity when a large amount of water vapor and sulfur dioxide are introduced, and can still maintain excellent reaction activity after high-temperature hydrothermal treatment.
[0026] The Cu-modified SAPO-34 composite material of the present invention can be used in the field of NH3-SCR denitration, such as the elimination of nitrogen oxides in automobile exhaust gas. BRIEF DESCRIPTION OF THE DRAWINGS
[0027] Figure 1 This is the XRD image of Cu-SAPO-34 obtained in Example 1;
[0028] Figure 2 The NO conversion rate image of Cu-SAPO-34 obtained in Example 1 at different temperatures;
[0029] Figure 3 This is the XRD image of Cu-SAPO-34 obtained in Example 2;
[0030] Figure 4 The NO conversion rate image of Cu-SAPO-34 obtained in Example 2 at different temperatures;
[0031] Figure 5This is the XRD image of Cu-SAPO-34 obtained in Example 3;
[0032] Figure 6 The NO conversion rate image of Cu-SAPO-34 at different temperatures obtained in Example 3;
[0033] Figure 7 This is the XRD image of Cu-SAPO-34 obtained in Example 4;
[0034] Figure 8 The NO conversion rate image of Cu-SAPO-34 obtained in Example 4 at different temperatures;
[0035] Fig. 9 This is the XRD image of Cu-SAPO-34 obtained in Example 5;
[0036] Fig.10 This is the NO conversion rate image of Cu-SAPO-34 obtained in Example 5 at different temperatures;
[0037] Fig.11 This is the Cu-SAPO-34N2 adsorption-desorption image obtained in Example 3;
[0038] Fig.12 The water and sulfur resistance test of Cu-SAPO-34 obtained in Example 3;
[0039] Fig.13 The synchrotron radiation results of Cu / SAPO-34 obtained in Example 3;
[0040] Fig.14 This is the XRD image of Cu-SAPO-34 obtained in Example 6;
[0041] Fig.15 The NO conversion rate image of Cu-SAPO-34 obtained in Example 6 at different temperatures;
[0042] Fig.16 This is the XRD image of Cu-SAPO-34 obtained in Example 7;
[0043] Fig.17 The NO conversion rate image of Cu-SAPO-34 obtained in Example 7 at different temperatures;
[0044] Fig.18 Figure 2 shows the NO conversion rate of Cu-SAPO-34 with different copper sources at different temperatures. DETAILED DESCRIPTION
[0045] The beneficial effects of the present invention are verified by the following examples.
[0046] Example 1: The preparation method of the Cu-modified SAPO-34 composite material of this example is carried out according to the following steps:
[0047] 1. First, dissolve 3.0g of pseudo-boehmite (the mass percentage of Al2O3 is 75%) in 30mL of deionized water, and stir on a magnetic stirrer at room temperature for 1h; then add 2.5mL of H3PO4 and continue stirring for 1h; then add 1.5g of white carbon black (the mass percentage of SiO2 is 88%) and continue stirring for 2h; then add 8mL of triethylamine (TEA) and continue stirring for 1h; then add 3mL of tetraethylenepentamine (TEPA) and stir for 2h; finally, add 1.0g of copper acetylacetonate and stir for 12h to obtain a sol-gel;
[0048] 2. After ultrasonic treatment, the sol-gel obtained in step 1 was transferred to a hydrothermal reactor, and then the hydrothermal reactor was placed in an oven at a temperature of 180°C for 24 hours for hydrothermal reaction. The product was washed with deionized water and ethanol three times each, centrifuged and dried in an oven at a temperature of 30°C for 8 hours to obtain a precursor;
[0049] 3. After the precursor is ground into powder, it is placed in a porcelain boat, placed in a high-temperature furnace, heated to 550°C and calcined for 5 hours to remove the template, thereby obtaining a Cu-modified SAPO-34 composite material, which is recorded as Cu-SAPO-34;
[0050] The XRD pattern of the Cu-SAPO-34 material obtained in this example is as follows: Figure 1 As shown, through Figure 1 It can be seen that the material has the CHA topological structure unique to SAPO-34, indicating that the addition of Cu does not destroy the structure of SAPO-34, and no diffraction peak of CuO is found, proving that Cu is highly dispersed.
[0051] The NO conversion rate of the Cu-SAPO-34 material obtained in Example 1 at different temperatures was tested, and the specific steps were:
[0052] The Cu-SAPO-34 material obtained in Example 1 was first granulated into 40-60 meshes, and the granulated sample was placed in a quartz tube and then placed in a fixed bed reactor. The reaction gas was a mixed gas of NO, NH3 and O2, wherein the concentration of NO was 1000ppm, the concentration of NH3 was 1000ppm, and the volume percentage of O2 was 5%; nitrogen was used as the balance gas, the total flow rate was controlled at 200mL / min, and the volume space velocity was GHSV=40000h -1 The NO conversion rate of the Cu-SAPO-34 material obtained in Example 1 at different temperatures was tested, and the NO conversion rate curves at different temperatures were as follows: Figure 2 As shown, from Figure 2It can be seen that the Cu-SAPO-34 material obtained in Example 1 has good denitration performance, and can achieve a conversion of more than 95% at 160°C to 400°C.
[0053] Example 2: This example is different from Example 1 in that "1.0 g of copper acetylacetonate" in step 1 is replaced by "1.2 g of copper acetylacetonate", and the other steps and parameters are the same as those in Example 1 to obtain a Cu-modified SAPO-34 composite material, which is recorded as Cu-SAPO-34 material.
[0054] The XRD pattern of the Cu-SAPO-34 material obtained in Example 2 is as follows: Figure 3 As shown, through Figure 3 It can be seen that the material has the CHA topological structure unique to SAPO-34, indicating that the addition of Cu does not destroy the structure of SAPO-34, and no diffraction peak of CuO is found, proving that Cu is highly dispersed.
[0055] The NO conversion rate of the Cu-SAPO-34 material obtained in Example 2 at different temperatures was tested using the same method as in Example 1. The NO conversion rate images of the Cu-SAPO-34 material at different temperatures are shown in FIG. Figure 4 As shown in the figure, it can be seen that Cu-SAPO-34 has good denitrification performance and can achieve a conversion of more than 95% at 150°C to 430°C.
[0056] Example 3: This example is different from Example 1 in that "1.0 g of copper acetylacetonate" in step 1 is replaced by "1.3 g of copper acetylacetonate", and the other steps and parameters are the same as those in Example 1 to obtain a Cu-modified SAPO-34 composite material, which is recorded as Cu-SAPO-34 material.
[0057] The XRD pattern of the Cu-SAPO-34 material obtained in Example 3 is as follows: Figure 5 As shown, through Figure 5 It can be seen that the material has the CHA topological structure unique to SAPO-34, indicating that the addition of Cu does not destroy the structure of SAPO-34, and no diffraction peak of CuO is found, proving that Cu is highly dispersed.
[0058] The NO conversion rate of the Cu-SAPO-34 material obtained in Example 3 at different temperatures was tested using the same method as in Example 1. The NO conversion rate images of the Cu-SAPO-34 material at different temperatures are shown in FIG. Figure 6 As shown in the figure, it can be seen that Cu-SAPO-34 has good denitrification performance and can achieve a conversion of more than 95% at 140°C to 430°C.
[0059] Example 4: This example is different from Example 1 in that "1.0 g of copper acetylacetonate" in step 1 is replaced by "1.4 g of copper acetylacetonate", and the other steps and parameters are the same as those in Example 1, to obtain a Cu-modified SAPO-34 composite material, which is recorded as Cu-SAPO-34 material.
[0060] The XRD pattern of the Cu-SAPO-34 material obtained in Example 4 is as follows: Figure 7 As shown, through Figure 7 It can be seen that the material has the CHA topological structure unique to SAPO-34, indicating that the addition of Cu does not destroy the structure of SAPO-34, and no diffraction peak of CuO is found, proving that Cu is highly dispersed.
[0061] The NO conversion rate of the Cu-SAPO-34 material obtained in Example 4 at different temperatures was tested using the same method as in Example 1. The NO conversion rate images of the Cu-SAPO-34 material at different temperatures are shown in FIG. Figure 8 As shown in the figure, it can be seen that Cu-SAPO-34 has good denitrification performance and can achieve a conversion of more than 95% at 150°C to 400°C.
[0062] Example 5: This example is different from Example 1 in that "1.0 g of copper acetylacetonate" in step 1 is replaced by "1.6 g of copper acetylacetonate", and the other steps and parameters are the same as those in Example 1 to obtain a Cu-modified SAPO-34 composite material, which is recorded as Cu-SAPO-34 material.
[0063] The XRD pattern of the Cu-SAPO-34 material obtained in Example 5 is as follows: Fig. 9 As shown, through Fig. 9 It can be seen that the material has the CHA topological structure unique to SAPO-34, indicating that the addition of Cu does not destroy the structure of SAPO-34, and no diffraction peak of CuO is found, proving that Cu is highly dispersed.
[0064] The NO conversion rate of the Cu-SAPO-34 material obtained in Example 5 at different temperatures was tested using the same method as in Example 1. The NO conversion rate images of the Cu-SAPO-34 material at different temperatures are shown in FIG. Fig.10 As shown in the figure, it can be seen that Cu-SAPO-34 has good denitrification performance and can achieve a conversion of more than 95% at 160°C to 400°C.
[0065] The Cu-SAPO-34 materials prepared in Examples 1 to 5 all achieved good denitration performance. Among them, the Cu-SAPO-34 prepared in Example 3 had the best denitration performance. The Cu-SAPO-34 prepared in Example 3 was subjected to nitrogen adsorption-desorption test, and the obtained nitrogen adsorption-desorption curve was as shown in FIG. Fig.11 As shown, from Fig.11 It can be seen that the catalyst has a type IV isotherm and an H3 type hysteresis loop, indicating that the catalyst has a mesoporous structure.
[0066] The water and sulfur resistance of the Cu-SAPO-34 prepared in Example 3 was tested. The specific steps were as follows: the Cu-SAPO-34 material obtained in Example 1 was first granulated to 40-60 meshes, the granulated sample was placed in a quartz tube, and then placed in a fixed bed reactor. The reaction gas was a mixed gas of NO, NH3 and O2, wherein the concentration of NO was 1000ppm, the concentration of NH3 was 1000ppm, and the volume percentage of O2 was 5%; nitrogen was used as the balance gas, the total flow rate was controlled at 200mL / min, and the volume space velocity was GHSV=40000h -1 On the basis of the above, the NO conversion rates were measured when 5% H2O, 10% H2O, 100ppm SO2, 200ppm SO2 and 100ppm SO2 and 5% H2O were introduced into the system. Fig.12 As shown, from Fig.12 It can be seen that even when 100 ppm SO2 and 5% H2O are introduced at the same time, the conversion rate is still maintained at 100%, proving that the catalyst has good resistance to water and sulfur.
[0067] The Cu-SAPO-34 prepared in Example 3 was subjected to synchrotron radiation testing, and the synchrotron radiation results obtained were as follows: Fig.13 As shown, from Fig.13 It can be seen that Cu / SAPO-34 has Cu-O bonds instead of Cu-Cu bonds, so the Cu / SAPO-34 obtained in Example 3 is an atomically dispersed catalyst.
[0068] Example 6: This example is different from Example 1 in that "1.0 g of copper acetylacetonate" in step 1 is replaced by "1.0 g of copper glycinate", and the other steps and parameters are the same as those in Example 1 to obtain a Cu-modified SAPO-34 composite material, which is recorded as Cu-SAPO-34 material.
[0069] The XRD pattern of the Cu-SAPO-34 material obtained in Example 6 is as follows: Fig.14 As shown, through Fig.14 It can be seen that the material has the CHA topological structure unique to SAPO-34, indicating that the addition of Cu does not destroy the structure of SAPO-34, and no diffraction peak of CuO is found, proving that Cu is highly dispersed.
[0070] The NO conversion rate of the Cu-SAPO-34 material obtained in Example 6 at different temperatures was tested using the same method as in Example 1. The NO conversion rate images of the Cu-SAPO-34 material at different temperatures are shown in FIG. Fig.15 As shown in the figure, it can be seen that Cu-SAPO-34 has good denitrification performance and can achieve more than 90% conversion at 150°C to 350°C.
[0071] Example 7: The difference between this example and Example 1 is that the "1.0 g of copper acetylacetonate" in step one is replaced by "8 mL of copper ethylenediamine dihydroxide", and the other steps and parameters are the same as those in Example 1, to obtain a Cu-modified SAPO-34 composite material, which is recorded as Cu-SAPO-34 material.
[0072] The XRD pattern of the Cu-SAPO-34 material obtained in Example 7 is as follows: Fig.16 As shown, through Fig.16 It can be seen that the material has the CHA topological structure unique to SAPO-34, indicating that the addition of Cu does not destroy the structure of SAPO-34, and no diffraction peak of CuO is found, proving that Cu is highly dispersed.
[0073] The NO conversion rate of the Cu-SAPO-34 material obtained in Example 7 at different temperatures was tested using the same method as in Example 1. The NO conversion rate images of the Cu-SAPO-34 material at different temperatures are shown in FIG. Fig.17 As shown in the figure, it can be seen that Cu-SAPO-34 has good denitrification performance and can achieve a conversion of more than 90% at 160°C to 400°C.
[0074] Comparative Example 1: This embodiment differs from Example 1 in that "1.0 g of copper acetylacetonate" in step 1 is replaced by "0.7 g of copper citrate", and the other steps and parameters are the same as those in Example 1, to obtain a Cu-modified SAPO-34 composite material, recorded as Cu-SAPO-34 material.
[0075] Comparative Example 2: This embodiment differs from Example 1 in that "1.0 g of copper acetylacetonate" in step 1 is replaced by "1.0 g of sodium copper chlorophyllin", and the other steps and parameters are the same as those in Example 1, to obtain a Cu-modified SAPO-34 composite material, recorded as Cu-SAPO-34 material.
[0076] Comparative Example 3: This embodiment differs from Example 1 in that "1.0 g of copper acetylacetonate" in step 1 is replaced by "1.5 g of copper quinoline", and the other steps and parameters are the same as those in Example 1, to obtain a Cu-modified SAPO-34 composite material, recorded as Cu-SAPO-34 material.
[0077] The same test method as in Example 1 was used to test the NO conversion rates of the Cu-SAPO-34 materials prepared in Example 6, Example 7, and Comparative Examples 1 to 3 at different temperatures. The obtained conversion rate curves are shown in FIG. Fig.18 As shown, the conversion rate of the Cu-SAPO-34 material prepared in Example 3 is also plotted on Fig.18 In, from Fig.18 It can be seen that the NO conversion rates of the six Cu-SAPO-34 materials with different copper sources are different at different temperatures. In Example 3, the Cu-SAPO-34 with copper acetylacetonate as the copper source has the best denitration performance, which can reach more than 95% conversion at 140°C to 430°C. The Cu-SAPO-34 with copper glycinate and copper ethylenediamine dihydroxide as the copper source has better denitration performance, which can reach more than 90% conversion at 150°C to 350°C and 160°C to 400°C, respectively. The performance of the Cu-SAPO-34 materials with copper citrate, sodium copper chlorophyllin and quinoline copper as the copper source is relatively poor.
[0078] The present invention uses low-priced white carbon black, pseudo-boehmite and phosphoric acid as Si, Al and P sources, and uses a copper organic complex with a special structure as a copper source. By adding the copper source, the distribution of Cu is adjusted to form a catalyst with atomic-level dispersed active sites, and the stability of the molecular sieve structure is significantly improved, thereby improving the low-temperature activity and hydrothermal stability. The preparation method is simple, the cost is low, and large-scale synthesis can be performed. At the same time, the catalyst exhibits high low-temperature SCR activity, N2 selectivity, excellent water and sulfur resistance, and good hydrothermal stability in the NH3-SCR denitration reaction.
Claims
1. A method for preparing a Cu-modified SAPO-34 composite material, characterized in that The method proceeds as follows:
1. Weigh pseudo-boehmite, H3PO4, white carbon, triethylamine, tetraethylenepentamine, and copper organic complex; wherein the mass ratio of pseudo-boehmite to white carbon is (1.1-2.7):1; the volume ratio of H3PO4 to the mass of white carbon is (1.3-2) mL:1 g; the copper organic complex is copper acetylacetonate, copper glycinate, or copper ethylenediamine dihydroxide; First, dissolve pseudo-boehmite in deionized water and stir on a magnetic stirrer at room temperature for 0 to 4 hours; then add H3PO4 and continue stirring for 0 to 4 hours; then add white carbon black and continue stirring for 2 to 2.5 hours; then add triethylamine and continue stirring for 0 to 4 hours; then add tetraethylenepentamine and stir for 2 to 2.5 hours; finally, add copper organic complex and stir for 8 to 16 hours to obtain sol-gel; 2. After ultrasonic treatment, the sol-gel obtained in step 1 is transferred to a hydrothermal reactor, and then the hydrothermal reactor is placed in an oven at a temperature of 180-200° C. for 24-48 hours for hydrothermal reaction, and the product is washed with deionized water and ethanol in turn, centrifuged and dried to obtain a precursor; 3. Grind the precursor into powder and place it in a porcelain boat, then place the porcelain boat in a muffle furnace, heat it to 550-580°C and calcine it for 5-6 hours to obtain a Cu-modified SAPO-34 composite material.
2. The method for preparing the Cu-modified SAPO-34 composite material according to claim 1, characterized in that: The mass percentage of Al2O3 in the pseudo-boehmite described in step 1 is ≥ 70%.
3. The method for preparing the Cu-modified SAPO-34 composite material according to claim 1 or 2, characterized in that: The mass percentage of SiO2 in the white carbon black described in step 1 is ≥85%.
4. The method for preparing the Cu-modified SAPO-34 composite material according to claim 1 or 2, characterized in that: The ratio of the mass of the white carbon black described in step 1 to the volume of triethylamine is 1 g: (3.3-6.7) mL.
5. The method for preparing the Cu-modified SAPO-34 composite material according to claim 1 or 2, characterized in that: The ratio of the mass of the white carbon black described in step 1 to the volume of tetraethylenepentamine is 1 g: (1.3-2) mL.
6. The method for preparing the Cu-modified SAPO-34 composite material according to claim 1 or 2, characterized in that: The mass ratio of white carbon black to copper acetylacetonate described in step 1 is 1:(0.6-1.4).
7. The method for preparing the Cu-modified SAPO-34 composite material according to claim 1 or 2, characterized in that: The mass ratio of white carbon black to copper glycinate described in step 1 is 1:(0.5-1).
8. The method for preparing the Cu-modified SAPO-34 composite material according to claim 1 or 2, characterized in that: The ratio of the mass of the white carbon black described in step 1 to the volume of copper dihydroxide of ethylenediamine is 1 g: (3.3-6.7) mL.
9. Application of the Cu-modified SAPO-34 composite material prepared by the method of claim 1, characterized in that: The application is to use Cu-modified SAPO-34 composite material as a catalyst in NH3-SCR denitrification reaction.
Citation Information
Patent Citations
Preparation method and application of catalyst for selectively catalytically reducing nitric oxide
CN109622029A
Preparation method of hierarchical pore Cu / SAPO-34 catalyst
CN111617801A
Eutectic catalyst, solid-state ion exchange preparation method and application thereof
CN111744547A
Cu / SAPO-34 molecular sieve catalyst as well as preparation method and application thereof
CN116273151A
Copper / chabazite-based catalyst with improved catalytic activity for reduction of nitrogen oxides
US20130266497A1